Serum exosomal microRNAs combined with alpha‐fetoprotein as diagnostic markers of hepatocellular carcinoma - Wang, Yurong; Zhang, Chunyan; Zhang, Pengjun; Guo, Guanghong; Jiang, Tao; Zhao, Xiumei; Jiang, Jingjing; Huang, Xueliang; Tong, Hongli; Tian, Yaping (Cancer medicine (Malden, MA), 2018)
Exosomal microRNAs have recently been studied as the potential diagnostic marker for various malignancies, including hepatocellular carcinoma (HCC). The aim of this study was to investigate serum exosomal microRNA profiles as HCC diagnostic marker. Transmission electron microscopy and Western blot were used to identify serum exosomes. Deep sequencing was performed to screen differentially expressed microRNAs between HCC (n = 5) and liver cirrhosis (LC, n = 5) groups. Three upregulated and two downregulated microRNAs were selected for qPCR analysis. The levels of selected microRNAs were normalized to Caenorhabditis elegans miR‐39 microRNA mimics. Serum exosomal level of miR‐122, miR‐148a, and miR‐1246 was further analyzed and significantly higher in HCC than LC and normal control (NC) groups (P < 0.001), but not different from chronic hepatitis group (P > 0.05). The receiver operating characteristic curve was used to evaluate the diagnostic performance of candidate microRNAs. Area under the curve (AUC) of miR‐148a was 0.891 [95% confidence interval (CI), 0.809–0.947] in discriminating HCC from LC, remarkably higher than alpha‐fetoprotein (AFP) (AUC: 0.712, 95% CI: 0.607–0.803). Binary logistic regression was adopted to establish the diagnostic model for discriminating HCC from LC. And the combination of miR‐122, miR‐148a, and AFP increased the AUC to 0.931 (95% CI, 0.857–0.973), which can also be applied for distinguishing early HCC from LC. miR‐122 was the best for differentiating HCC from NC (AUC: 0.990, 95% CI, 0.945–1.000). These data suggest that serum exosomal microRNAs signature or their combination with traditional biomarker may be used as a suitable peripheral screening tool for HCC. Significantly higher levels of serum exosomal miR‐122, miR‐148a, and miR‐1246 were found in subjects with hepatocellular carcinoma (HCC) than liver cirrhosis (LC) and normal control (NC). And the combination of exosomal microRNAs and alpha‐fetoprotein (AFP) yielded a better diagnostic power than AFP in discriminating subjects with (early) HCC from LC. Exosomal miR‐122 had the best diagnostic performance in discriminating HCC from NC subjects.